Replacing knowledge management practice with knowledge sharing initiatives in public sector organizations: A social exchange theory perspective / Noor Azreen Mohd Khushairi ... [et al.] - Mohd Khushairi, Noor Azreen (2024)
Knowledge management (KM) faces challenges in public organizations due to several factors, such as hierarchical organizational structure, cultural barriers, and resistance to change, which can hinder its effectiveness and suitability. Public sector organizations have cultures that value transparency, inclusivity, and collaboration. In this context, knowledge sharing (KS) replaces knowledge management (KM) since the concept aligns well with the public sector organizations' cultural values, creating a supportive environment where employees feel empowered to contribute and collaborate effectively. Thus, this paper proposes the significance of adopting the concept of knowledge sharing (KS) compared to traditional knowledge management (KM) framed within the context of Social Exchange Theory (SET) in public sector organizations. A quantitative design is utilized through two stages of data collection involving 304 respondents from five selected public sector organizations. The finding indicates that Knowledge Sharing (KS) is a significant mediator of the SET framework for public sector organizations, while Knowledge Management (KM) is not. Understanding how knowledge-sharing exchanges organizational effectiveness and employee engagement is crucial for public organizations seeking to improve their knowledge management strategies.